Education service: a strategy for the management of drug safe - Duarte, Lucélia Maria Carla Paulo da Silva (2015)
Insecurity in the medication system is a public health problem that besides the damage to the patient’s health, generates economic loss by unnecessary costs, since the errors are preventable. This study aims to describe the experience of developing a continuing education workshop for safety in medication administration. This is an experience report conducted in a university hospital in the Rio Grande do Norte. The target audience was the nursing staff consists of 32 employees. The educational activity used as a pedagogical base the Theory of Curriculum. As a result, participants identified three categories referring to the problems and proposed four categories of solutions / security barrier. Regarding the word synthesis, they were grouped subsequently into three categories according to their denotative. It concludes that educational activities provided moments of reflection about the care practices and managing their risks, and make active subjects participating in the search for solutions of the problems. In addition, it is recommended, from that experience, continuing education as a sponsor strategy of safe practices based on scientific evidence and good conduct.